A comparative thermoeconomic evaluation of three biomass and biomass-natural gas fired combined cycles using organic Rankine cycles. (10th September 2017) - Moharamian, Anahita; Soltani, Saeed; Rosen, Marc A.; Mahmoudi, S.M.S.; Morosuk, Tatiana
Abstract: Thermodynamic and thermoeconomic analyses are reported of three proposed biomass, and biomass-natural gas, combined cycles: biomass integrated co-fired combined cycle, biomass integrated post-firing combined cycle and externally fired combined cycle. Various working fluids are assessed for the bottoming organic Rankine cycle. Plants using R141b in the bottoming cycles are observed to have the highest energy and exergy efficiencies. Varying the turbine inlet temperature of the organic Rankine cycle affects its mass flow rate for all plants negligibly. Each plant exhibits optimal power performance with respect to some compressor pressure ratio; this occurs at values of about 11, 12 and 9 for the externally fired, the biomass integrated co-fired, and the biomass integrated post-fired combined cycles, respectively. Increasing the organic Rankine cycle turbine inlet pressure affects negligibly the unit product cost for the externally fired combined cycle but increases and reduces it for the biomass integrated co-fired and biomass integrated post-fired combined cycles, respectively; for the externally fired combined cycle there are optimal points, but the cost increases for the biomass integrated co-fired combined cycle and decreases for the biomass integrated post-fired combined cycle. Overall, the highest energy and exergy efficiencies are exhibited by the biomass integrated post-fired combined cycle at 0.37 and 0.34 respectively and the lowest by the externally fired combined cycle at 0.36 and 0.21 respectively. Also, the highest organic Rankine cycle mass flow rate is observed for the externally fired combined cycle (18 kg/s), followed by the biomass integrated co-fired combined cycle (17 kg/s) and the biomass integrated post-fired combined cycle (16 kg/s). The complete unit product cost is lowest for the externally fired combined cycle (5 $/GJ) and highest for the biomass integrated post-fired combined cycle (20 $/GJ). Highlights: The utilization of gasified biomass in three configurations is analyzed. The performance of organic Rankine and steam cycles is contrasted. Exergy and thermoeconomic analyses are applied to enhance cycle understanding. Using R141b in the bottoming cycles leads to the highest efficiencies.